Effect of Longevity on Economic Growth, Accounting for Variability in Demographic Transition: Evidence for Pakistan using ARDL Bounds Testing Approach - Mudasser, Muhammad; Yiridoe, Emmanuel K. (SEISENSE (PRIVATE) LIMITED, 2024)
Rising longevity due to access to better health services affects the growth and composition of the population differently than birth rates. In addition, empirical evidence of the effects of rising longevity on standards of living is ambiguous. From the perspective of developing nations, it is important to understand how rising longevity affects national prosperity, as this allows governments to develop programs for increasing investment in the health sector. This study explicitly tested varying intertemporal impacts of rising longevity on the GDP per capita of Pakistan between 1967 and 2020. An Autoregressive Distributed Lag (ARDL) bounds testing approach to cointegration was used to estimate and compare short-run and long-run estimates of longevity. The results indicated that a 1% increase in longevity increased the growth rate of GDP per capita in Pakistan by 0.64% in the long-run. In addition, a 1% increase in life expectancy at birth above 62 years increased economic growth by an additional 0.009%. In general, the estimated effect of increased longevity varied by stages of demographic transition in Pakistan.